2019
DOI: 10.1172/jci124853
|View full text |Cite
|
Sign up to set email alerts
|

APOE4-mediated amyloid-β pathology depends on its neuronal receptor LRP1

Abstract: (GB). pathology (9). Thus, it is predicted that neuronal LRP1 deficiency also prevents apoE4-related Aβ aggregation at an early stage. One limitation of our study is that we could not analyze Aβ pathology in older mice due to a reduced survival rate at the age of 12 months, for unknown reasons. At older ages, neuronal LRP1 deficiency may accelerate Aβ deposition independently of apoE4. In this regard, suppressing LRP1 levels may not be a suitable approach as potential AD therapy because LRP1 plays a critical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 28 publications
(30 reference statements)
2
97
1
Order By: Relevance
“…While ApoE did not play a role in developing the maximal fibrosis in bleomycin-treated lung, it was indispensable to the resolution of this pathology. Mechanistically, we found that ApoE was capable of binding to type I Collagen and mediating collagen phagocytosis via the ApoE receptor, low-density lipoprotein receptor-related protein 1 (LRP1) (22). Our data reveal that a previously unappreciated role of the monocyte-derived subset of AMs may not just passively respond with phenotype change during injury, but they also actively participate in resolving fibrosis and maintaining lung homeostasis.…”
Section: Introductionmentioning
confidence: 76%
“…While ApoE did not play a role in developing the maximal fibrosis in bleomycin-treated lung, it was indispensable to the resolution of this pathology. Mechanistically, we found that ApoE was capable of binding to type I Collagen and mediating collagen phagocytosis via the ApoE receptor, low-density lipoprotein receptor-related protein 1 (LRP1) (22). Our data reveal that a previously unappreciated role of the monocyte-derived subset of AMs may not just passively respond with phenotype change during injury, but they also actively participate in resolving fibrosis and maintaining lung homeostasis.…”
Section: Introductionmentioning
confidence: 76%
“…ApoE can directly bind to Aβ amino-acid residues [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], subsequently forming apoE/Aβ complex within neurons and extracellular space [31][32][33]. Co-deposition of apoE with Aβ is a key step for Aβ brillization and plaque formation [50,51]. Therefore, blocking apoE/Aβ interaction may be a promising strategy for improving clearance of soluble Aβ from the brain, and preventing the onset of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of a mutated form of human App precursor protein in a transgenic mouse model leads to significant App deposition in the brain, but these deposits are substantially reduced by performing the same experiment in mice with an ApoE knockout background (Berul et al, 1999, Fagan et al, 2002. ApoE4 is the single largest genetic risk factor for sporadic AD and promotes disease pathology by seeding Aβ aggregation in the brain, but recent data indicate that AD risk can be reversed by loss of the neuronal receptor Lrp1 (Tachibana et al, 2019) which was identified in our experiments as undergoing active synthesis in murine brain (average heavy/light ratio: 4.9±0.2, average emPAI value: 1.8±0.2). These data indicate that pSIVOM can provide novel insight into the biology of human ApoE isoforms through study of human ApoEs knock in mouse brain proteomics, which is central to AD pathology in human patients.…”
Section: Discussionmentioning
confidence: 99%